A video atlas of TOMS ozone data, 1978-88 - Chesters, D.; Krueger, A. J. (1989)
The Total Ozone Mapping Spectrometer (TOMS), on-board NASA's Nimbus-7 weather satellite, has been observing ozone over the earth once daily for the last 10 yr. A time-lapse atlas of 3440 color-coded images drawn from the TOMS archive from 1978 to 1988 has been visualized on a standard VHS videotape that is now available from NASA. The rapid and complex ozone variations presented demonstrate the difficulty of separating man-induced climate changes from natural variability. This article presents a few images from the atlas and describes interesting features in the animation, such as the correlation between ozone and 'the weather', and the recent deepening of the annual ozone hole over the South Pole. Originally intended as a browsing tool for the TOMS digital database, the videotape is a vivid presentation of the earth's atmospheric dynamics and chemistry that is recommended for scientists, educators, policy makers, and citizens concerned about the global environment.